Cannabinoid CB(2) receptors in the mouse brain: relevance for Alzheimer’s disease - López, Alicia (J Neuroinflammation, 2018)
BACKGROUND: Because of their low levels of expression and the inadequacy of current research tools, CB(2) cannabinoid receptors (CB(2)R) have been difficult to study, particularly in the brain. This receptor is especially relevant in the context of neuroinflammation, so novel tools are needed to unveil its pathophysiological role(s). METHODS: We have generated a transgenic mouse model in which the expression of enhanced green fluorescent protein (EGFP) is under the control of the cnr2 gene promoter through the insertion of an Internal Ribosomal Entry Site followed by the EGFP coding region immediately 3′ of the cnr2 gene and crossed these mice with mice expressing five familial Alzheimer’s disease (AD) mutations (5xFAD). RESULTS: Expression of EGFP in control mice was below the level of detection in all regions of the central nervous system (CNS) that we examined. CB(2)R-dependent-EGFP expression was detected in the CNS of 3-month-old AD mice in areas of intense inflammation and amyloid deposition; expression was coincident with the appearance of plaques in the cortex, hippocampus, brain stem, and thalamus. The expression of EGFP increased as a function of plaque formation and subsequent microgliosis and was restricted to microglial cells located in close proximity to neuritic plaques. AD mice with CB(2)R deletion exhibited decreased neuritic plaques with no changes in IL1β expression. CONCLUSIONS: Using a novel reporter mouse line, we found no evidence for CB(2)R expression in the healthy CNS but clear up-regulation in the context of amyloid-triggered neuroinflammation. Data from CB(2)R null mice indicate that they play a complex role in the response to plaque formation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-018-1174-9) contains supplementary material, which is available to authorized users.